WITNESS PROTECTION IN ANTI-MONEY LAUNDERING CASES: AN INTERNATIONAL PERSPECTIVE - Makhubele, Ethel; Albertus, Chesné (Journal of Anti-Corruption Law, 2023)
In recent years money laundering has become a global phenomenon which plagues the economies of many states. The methods of laundering money have equally evolved alongside advanced technologies, the proliferation of migration and the realities of instant communications. The complexity of laundering money has often made the detection, investigation and prosecution of these crimes challenging and at times, impossible. To boot, the perpetrators of money laundering are usually powerful and dangerous persons who will do anything to avoid the loss of their illegally obtained wealth and to escape the justice system. Witnesses are often vital to investigating and prosecuting cases which involve money laundering. They are, however, at great risk of being harmed and even killed for giving evidence against the powerful perpetrators. There is thus a pressing need for witness in money laundering cases to be afforded protection by the state. The failure to afford effective protection to witnesses have major implications not only for the criminal justice system, but also for witnesses, their families and communities. This article argues that given these facts, there is a need for comprehensive and effective witness protection in cases involving money laundering. The article sketches the existing international legal framework aimed at protecting witnesses and analysis the relevant laws. It furthermore , places the spotlight on some of the main institutions which ought to afford protection to witnesses. It reaches findings and makes recommendations for the improved protection of witnesses in money laundering cases.